The concept of rulership according to Al-Ghazali in Nasihat Al-Muluk and Marchiavelli in The Prince : a comparative analysis - Nur Adillah binti Omar (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2018)
The objective of this study is to analyse the concept of rulership according to the perspectives of two scholars from the area of political philosophy, namely al-Ghazali and Machiavelli. It is important to fully understand the concept of rulership according to these two scholars as presented in their books Naṣiḥat al-Muluk and The Prince in order to know the basis of political systems advocated by al-Ghazali and Machiavelli in relation to the advice they gave to their respective rulers in governing the states during their time. It is necessary to research on this since their respective views on rulership are not only for the people who lived in the past, but also for the present and future generations. Of course, both scholars have contradictory views. Al-Ghazali upholds religion as the foundation of his political approach, whereas Machiavelli is a secular thinker, who detaches religion and morality for the foundation of his political approach. However, both scholars use the same framework of political system, which is the authoritarian political system framework, in giving advice to the rulers in governing their states. Thus, this dissertation analyses the concept of rulership in order to justify the authoritarian style of political system that has been theorised by both al-Ghazali and Machiavelli, based on Naṣiḥat al-Muluk and The Prince respectively using Juan Linz's framework of authoritarian political system which are limited pluralism, mentally, mobilization and leadership.